Describing auxin solid state intermolecular interactions using contact descriptors, shape property and molecular fingerprint: comparison of pure auxin crystal and auxin-TIR1 co-crystal - Etse, Kodjo Djidjole; Etse, Koffi Senam; Quashie, Marie-Luce Akossiwoa (European Journal of Chemistry, 2022)
This work reports for the first time, the analysis of intermolecular interactions in crystal structures of auxin (Indole-3-acetic acid) crystallized as pure sample (Aux-A) or co-crystallized with transport inhibitor response 1 (Aux-B). Using crystal packing of pure auxin and a cluster of residues in a radius of 6 Å around this ligand in the transport inhibitor response 1 binding domain, various properties were calculated and mapped on the Hirshfeld surface (HS). The HSs of the two molecules are characterized by close parameters of volume, area, globularity, and asphericity revealing the efficiency of the considered cluster. The HS mapped over descriptors like de, di and dnorm showed red spots corresponding to hydrogen bonds contacts. In addition to the shape index and curvedness descriptors, the results highlight weak interactions stabilizing the auxin structures. The analyses of electrostatic potential, electron density, and deformation density maps confirm the slightly change in the electron donor and acceptor groups localization. Furthermore, the molecular fingerprint analyses revealed a notable discrepancy in the shape and percentage value of the various contacts. Decomposition of the fingerprint shows that the contributions of important contacts (H···H, H···O, and O···O) are higher in Aux-B than in Aux-A. Finally, the quantitative approach by the determination of the molecular interaction energies of the two structures in their respective crystallographic environment revealed that Aux-A is slightly more stabilized than Aux-B.